2020
DOI: 10.3389/fimmu.2020.578648
|View full text |Cite
|
Sign up to set email alerts
|

Human Commensal Prevotella histicola Ameliorates Disease as Effectively as Interferon-Beta in the Experimental Autoimmune Encephalomyelitis

Abstract: Gut microbiota has emerged as an important environmental factor in the pathobiology of multiple sclerosis (MS), an inflammatory demyelinating disease of the central nervous system (CNS). Both genetic and environmental factors have been shown to play an important role in MS. Among genetic factors, the human leukocyte antigen (HLA) class II allele such as HLA-DR2, DR3, DR4, DQ6, and DQ8 show the association with the MS. We have previously used transgenic mice expressing MS susceptible HLA class II allele such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 50 publications
2
21
0
1
Order By: Relevance
“…[56][57][58]65 These results were consistent across all three P. histicola treatments. 56,57,58 L. reuteri was also represented in multiple studies and was shown to exacerbate EAE in both, either when administered alone (in the context of a normal microbiome) 37 or in combination with Allobaculum (in a dualcolonization gnotobiotic model). 38 For studies that analyzed the microbiome, commensal therapy groups had a general microbiome shift toward pre-EAE states following treatment, including an increased relative abundance of Bacteriodetes, Firmicutes, Prevotella spp., and Lactobacillus spp.…”
Section: Major Trendssupporting
confidence: 69%
See 4 more Smart Citations
“…[56][57][58]65 These results were consistent across all three P. histicola treatments. 56,57,58 L. reuteri was also represented in multiple studies and was shown to exacerbate EAE in both, either when administered alone (in the context of a normal microbiome) 37 or in combination with Allobaculum (in a dualcolonization gnotobiotic model). 38 For studies that analyzed the microbiome, commensal therapy groups had a general microbiome shift toward pre-EAE states following treatment, including an increased relative abundance of Bacteriodetes, Firmicutes, Prevotella spp., and Lactobacillus spp.…”
Section: Major Trendssupporting
confidence: 69%
“…56 Similar to probiotic therapy, reduced proinflammatory and increased antiinflammatory immune responses were observed in each of the commensal studies. Specifically, studies found decreased IL-17-and IFN-γ-producing CD4 + T cells, 56,58,65 T H 17 cells, 65 and IL-17, 56,62,70 IFN-γ, 56,70 IL-23, 56 and IL-12 70 cytokines; and increased IL-10, 56,62,70 TGF-β, 56 and Tregs. [56][57][58]65 These results were consistent across all three P. histicola treatments.…”
Section: Major Trendsmentioning
confidence: 99%
See 3 more Smart Citations